Dakota (Dakon Matematika) Sebagai Media Penanaman Konsep KPK dan FBB di Sekolah Dasar - Muhammad Hatim; Misbahul Hadi; Moch Miftachul Huda (EduBasic Journal: Jurnal Pendidikan Dasar, 2019)
Mathematics teaching nowadays still requires students to memorize formulas but does not provide an understanding of concepts.Teachers who only teaches mathematics monotonously will result in students’ learning motivation decreasing. They need to explore the use of media to help students experiencing a meaningful and practical concept. This study tried to explore the potential of Dakon traditional game as media to encourage students’ motivation and concept understanding. Dakon is proposed as a media to help students understand the material conceptually by fun learning. Dakon Matematika (Dakota) is presented as one of the media that allows students in understanding Least Common Multiple (KPK) and Greatest Common Divisor (FPB) concept in elementary school. Dakon Matematika (Dakota) potentially can foster student learning motivation because besides studying mathematics it also introduces students to one of the Indonesian traditional games that are almost abandoned. This result of study promoted the Dakon and other traditional games to in mathematic learning. Some research on the use of Dakon in mathematics learning also showed the potential use of Dakon Matematikagames in learning mathematics, especially in the KPK and FPB material at elementary school level.